(untitled) (Medical science of Uzbekistan, 2024)
This review article is aimed at studying the effectiveness of preserving the alveolar process during tooth extraction. Based on the literature, all methods for preserving alveolar bone volume have been studied. Based on the literature studied, conclusions were drawn about improving the preservation of alveolar bone after tooth extraction.